Question about a Functional Equation.

Calculus Level 3

Is there a nowhere continuous function satisfying the following functional equation? f ( x 1 ) + f ( x + 1 ) = 3 f ( x ) f(x-1)+f(x+1)=\sqrt{3}f(x) Justify your answer.


Note: A real-valued function defined on the set of all real numbers is said to be nowhere continuous if it is discontinuous at any real number.

Inspiration

No Yes

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Arturo Presa
May 30, 2018

Let g ( x ) = sin ( π 6 x ) . g(x)= \sin(\frac{\pi}{6}x). Then it is easy to see that g ( x ) g(x) satisfies the given functional equation. Now, let us define, f ( x ) = { g ( x ) if x is irrational 2 g ( x ) if x is rational, but not integer g ( x 1 ) if x is any integer f(x)= \begin{cases} g(x) & \text{if} \; x\text{ is irrational } \\ 2g(x) & \text{if} \; x\; \text{is rational, but not integer} \\ g(x-1) & \text{if}\; x \;\text{ is any integer } \end{cases} Then it can be proved that f ( x ) f(x) satisfies the functional equation and is nowhere continuous.

The proof of the fact that f ( x ) f(x) satisfies the functional equation is very simple and can be derived from the fact that g ( x 1 ) + g ( x + 1 ) = 3 g ( x ) g(x-1)+g(x+1)=\sqrt{3} g(x) for all real values of x , x, but there is a detail that we should not ignore when writing a detailed proof. This important point is the fact that if x x is irrational, so are x 1 x-1 and x + 1 x+1 . Additionally, if x x is a non-integer rational number, so are x 1 x-1 and x + 1 , x+1, and something similar in the case that x x is just an integer.

Now, lets prove that f ( x ) f(x) cannot be continuous at any point.

Case 1. (When x x is irrational). We can find a sequence x n {x_n} formed by non-integer rational numbers, such that lim n x n = x . \lim_{n\rightarrow \infty }x_n =x. Then lim n f ( x n ) = lim n 2 g ( x n ) = 2 g ( x ) g ( x ) = f ( x ) . \lim_{n\rightarrow \infty }f(x_n)=\lim_{n\rightarrow \infty }2g(x_n)=2g(x)\neq g(x)= f(x). Notice that g ( x ) 2 g ( x ) g(x)\neq2g(x) for any irrational value of x , x, because 2 g ( x ) = g ( x ) 2g(x)=g(x) if and only if x x is an integer number multiple of 6.

Case 2. (When x x is a non-integer rational number). We can find a sequence x n {x_n} formed by
irrational numbers, such that lim n x n = x . \lim_{n\rightarrow \infty }x_n =x. Then lim n f ( x n ) = lim n g ( x n ) = g ( x ) 2 g ( x ) = f ( x ) . \lim_{n\rightarrow \infty }f(x_n)=\lim_{n\rightarrow \infty }g(x_n)=g(x)\neq 2g(x)= f(x). The reason why the inequality takes place is similar to the one in the Case 1.

Case 3. (When x x is an integer). We can find a sequence x n {x_n} formed by
non-integers rational numbers, such that lim n x n = x . \lim_{n\rightarrow \infty }x_n =x. Then lim n f ( x n ) = lim n g ( x n ) = g ( x ) g ( x 1 ) = f ( x ) . \lim_{n\rightarrow \infty }f(x_n)=\lim_{n\rightarrow \infty }g(x_n)=g(x)\neq g(x-1)= f(x). The inequality g ( x ) g ( x 1 ) g(x)\neq g(x-1) takes place for any integer value of x , x, because the solutions of the equation g ( x ) = g ( x 1 ) g(x)= g(x-1) are the numbers of the form 6 n 5 / 2 , 6 n - 5/2, where n n is an arbitrary integer.

Therefore, this proves that the functions f f is not continuous at any point.

Remark. The function f ( x ) = { g ( x ) if x is irrational 2 g ( x ) if x is rational f(x)= \begin{cases} g(x) & \text{if} \; x \; \text{is irrational } \\ 2g(x) & \text{if} \; x \; \text{ is rational} \end{cases} would not be nowhere continuous. Can you find out why?

Department 8
May 31, 2018

We have f ( x 1 ) + f ( x + 1 ) = 3 f ( x ) f(x-1) + f(x+1) = \sqrt{3}f(x) So in easy language sum of two f's is nothing but equal to the root 3 times the mean of the argument of f's.

So plugging x = 0 , 1 , 1 x=0, 1, -1 we get. f ( 1 ) + f ( 1 ) = 3 f ( 0 ) f ( 0 ) + f ( 2 ) = 3 f ( 1 ) f ( 2 ) + f ( 0 ) = 3 f ( 1 ) f(-1)+f(1)=\sqrt{3}f(0) \\ f(0)+f(2)=\sqrt{3}f(1) \\ f(-2)+f(0)=\sqrt{3}f(-1) \\ Adding all we get ( 2 3 ) f ( 0 ) + f ( 2 ) + f ( 2 ) = ( 3 1 ) ( f ( 1 ) + f ( 1 ) ) ( 2 3 ) f ( 0 ) + 3 f ( 0 ) = ( 3 3 ) f ( 0 ) (2-\sqrt{3})f(0)+f(2)+f(-2)=(\sqrt{3}-1)(f(-1)+f(1)) \\ (2-\sqrt{3})f(0)+\sqrt{3}f(0)=(3-\sqrt{3})f(0) So there may be an equation such that f(0) is not 0 proving it as a nowhere continuous function.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...